PENDEKATAN ABCD (ASSET-BASED COMMUNITY DEVELOPMENT) DALAM PENGEMBANGAN PENDIDIKAN ISLAM - Abdurrahman (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
The Asset-Based Community Development (ABCD) approach offers an alternative to strengthen Islamic education by utilizing the strengths and assets that already exist within the community. This article discusses the history, definition, main principles, and application of ABCD in Islamic education. Initially, this approach emerged from efforts to address problems in poor communities in the United States. ABCD focuses on the strengths and potential of the community, not its shortcomings. This approach emphasizes the utilization of individual assets, associations, institutions, physical assets, and connections to achieve common goals. The main principles of ABCD are based on hidden talents, building networks, residents as main actors, inclusive leadership, and so on. The ABCD approach consists of five stages: asset mapping, building relationships, mobilizing community members, forming core groups, and utilizing external resources. In the development of Islamic education, ABCD can be applied to establish Islamic educational institutions, strengthen the role of madrasahs/Islamic schools, develop Islamic education curricula, and improve teacher quality.